Software for anthropometric assessment providing indexes of interest for health and sport - Albert, F.; Ortega, F.; Ruiz, J.; Castillo, M.; Gutiérrez, A. (International Journal of Computer Science in Sport, 2002)
Body composition assessment is of specific interest for health and sport practice. Several studies have described the statistical link between some anthropometric parameters and the risk for cardiovascular disease. Therefore, to dispose of simple and reliable anthropometric measures to be applied in population studies it is essential. Since body composition is determinant for athletic performance, these measures can also be applied to sportsmen. Underwater densitometry, isotopic dilution, electric impedanciometry of single or multiple frequency are some instruments to assess body composition. However, they are too expensive, complex or rather difficult to apply in population studies. In addition, its high economic cost precludes its availability to modest sport teams or athletes who practice sports without external funding.